Hướng hợp tác mong đợi trong lĩnh vực giáo dục Hàn - Việt thời gian tới - Soo, Bae Yang (VNU Journal of Science: Social Sciences and Humanities, 2004)
After established diplomatic relations with Vietnam in Dec. 1992, educational cooperation between Korea and Vietnam is developing day by day. The point of this article is searching "Directions of educational cooperation between Vietnam and Korea in the upcoming time’*. In order to reach the goal, at first, I scanned relationship in Education and Cultural cooperation of both country before 2002. And then I propose "Credit cross registration system” for more developing educational cooperation between Vietnamese University and Korean University in the upcoming time. In order to encourage Credit cross registration system, Korean government must be deregulate some legal system such as part-time job permission, simplified immigration procedure...etc.